The Effect of Internet Banking Use and Customer Protection Against Cyber Crime at Bank Rakyat Indonesia - Muhammad Agreindra, Helmiawan; Ade Iskandar, Nasution (2022)
With the very rapid development of technology that helps humans in carrying out their activities, one of them in the banking world has emerged a product in the banking world, namely internet banking. The problem with technological developments is the higher the number of crimes that occur in the internet banking process. This study uses a quantitative research method with a case study of one of Indonesia's national banks, namely Bank BRI specific in BRI KC Majalaya. This study found that the use of internet banking has a significant effect on cybercrime at Bank BRI KC Majalaya and consumer protection has a significant effect on cybercrime.